Successful Positive Health Impact of Nasal Surgery on Comorbid Difficult-to-Treat Chronic Rhinosinusitis and Severe Obstructive Sleep Apnea After Failed Medical Therapy - Jin-Ing Lin (Journal of Sleep Medicine, 2026)
Obstructive sleep apnea (OSA) is a common contributor to hypertension and is strongly associated with chronic rhinosinusitis (CRS) development. OSA and CRS have a bidirectional causality. OSA causes systemic tissue hypoxia and increases liability to infection and chronic inflammation. CRS reduces nasal nitric oxide release and pulmonary vasodilation and increases pulmonary arterial pressure. Our patient had obstruction at two subsites of the upper airway: static intranasal obstruction caused by CRS with an exophytic intranasal soft tissue mass and dynamic circumferential collapse of the velopharynx. Together, these findings led to further destabilization of the airway, persistent sleep dysfunction even with positive airway pressure (PAP) therapy, PAP intolerance, and inability to achieve an apnea-hypopnea index (AHI) of less than 10. The postsurgical AHI during PAP significantly declined to 5. The clinical significance of determining the subsequent need for surgical intervention in patients with PAP intolerance and a less optimal AHI is largely based on individualized physiological or pathological upper airway obstruction, including the affected airway subsites, collapse patterns, and severity. Identifying appropriate candidates is also important.